Dural Arteriovenous Fistula - A Review - Khan, Sharif Uddin; Siddiqui, Md Mahmudur Rahman; Rahman, Kazi Mohibur; Hoque, Md Azharul; Mondol, Md Badrul Alam; Habib, Mansur; Mohammad, Quazi Deen (Journal of Medicine, 2010)
DOI: 10.3329/jom.v11i2.5464 J MEDICINE 2010; 11 : 159-166